Strategi Komunikasi Kementerian Agama Indonesia Agar Keluar dari 20 Negara yang Dilarang Masuk Arab Saudi - Junaidi Junaidi (PROPAGANDA, 2022)
The Saudi government's decision to close access for Indonesia to be allowed to enter its territory made Indonesia for the second time cancel its annual pilgrimage, namely the pilgrimage. This study aims to identify and describe the communication strategy of the Ministry of Religion (Kemenag) so that Indonesia is not included in the 20 countries that are prohibited from entering Saudi Arabia. Because some countries whose COVID-19 numbers are higher or equal to Indonesia are not included in the 20 banned countries. To what extent is the communication strategy developed by the Ministry of Religion in order to convince Saudi Arabia that the implementation of Indonesian health protocols is very strict. Are the policies of the Ministry of Religion of the Republic of Indonesia in line with the policies of the Government of Saudi Arabia. This study also took samples of several news reports according to media/media framing from Republika.co.id and several news stories from other media that were relevant to answer this research. This study shows that the Ministry of Religion's communication policies and strategies have not optimally involved civil society groups. And the communication strategy developed by the government and organizations does not show good organized interests.